Perlindungan Hukum Terhadap Perempuan Korban KDRT(Kajian Terhadap Implementasi Keadilan Restoratif) - Friderika Friska Telaumbanua; Helfira Citra (CV. ITTC INDONESIA, 2023)
The percentage increase in domestic violence cases that changes from year to year illustrates that resolving cases using restorative justice efforts is less efficient. The author is interested in knowing the concepts and principles of restorative justice regulated in Indonesian legislation, especially in the context of legal protection for women victims of domestic violence and the author wants to know whether there is a discrepancy between the principles of restorative justice and the legal norms that apply in handling cases. Domestic Violence. The author uses a normative juridical approach with descriptive analytical research characteristics, using secondary data sourced from literature review. The concept of restorative justice focuses on resolving cases that focus on a dialogue process involving the perpetrator, victim and the perpetrator/victim's family, as well as related parties to jointly create a fair and balanced case resolution for both the victim and the perpetrator, by prioritizing recovery in the circumstances of all , the principles used in resolving cases through restorative justice efforts are the principles of recovery and reconciliation, the principles of participation and collaboration, the principles of responsibility and accountability, the principles of personal growth and behavior change, the principles of a holistic approach. In its implementation, a discrepancy arises between the principles of restorative justice and legal norms in Indonesia, domestic violence crimes are generally carried out with an element of intent, this is contrary to one of the material requirements that must be fulfilled in handling criminal cases through restorative justice.